Sunflower (Helianthus annuus) for Phytoremediation of Zinc in Hydroponic System / Zainab Razali …[et al.] - Razali, Zainab; Abd Wahab, Muhammad Faris; Md Kawi, Roejhan; Omar, Megawati; Chay Tay, Chia (Universiti Teknologi MARA Shah Alam, 2020)
It has been noted that zinc contamination is hazardous, which induces researchers to seek new means to overcome it. One of the methods is to employ the sunflower plant to eliminate zinc in soil. However, there is insufficient information about zinc phytoremediation by sunflowers in the hydroponic system. Hence in this study, a 15-day experiment was conducted using zinc concentrations of 0, 10, 20, and 30 mg/L in a hydroponic system to investigate the effect of zinc towards the sunflower. The effects of zinc concentration on the plant growth performance (length of root, length of the stem, and the number of leaf), zinc uptake, and zinc translocation were evaluated. The findings showed that the plant growth was stunted but tolerated to a zinc stress condition, where the zinc concentrations had affected the growth of the sunflower root, length, and stem, and the zinc uptake significantly (p<0.05). It was also found that there was a significant variation of root length and zinc uptake in leaf within certain phases statistically (p<0.05). Then the translocation factor was found significantly different for the time parameter but not the zinc concentrations (p<0.05). Therefore, this experiment concluded that the sunflower plant was highly tolerant of zinc and able to remove the zinc from contaminated environments. Lastly, this study showed that sunflowers are the potential to phytoremediate zinc in a hydroponic system.